Numerical Study of the Combustion of CH4-C3H8/ Air: Application to a Combustion Chamber with Two Coaxial Jets - Mohamed El Hadi Attia (International Journal of Energetica)
In this study, we studied numerically the non-premixed combustion provided by two coaxial methane-propane/air jets in a 3D cylindrical combustion chamber. To study this kind of phenomenon we used a special treatment of the mathematical model and we chose two models of computation PDF and LES. In order to find the aero-thermo-chemical characteristics in the burner, namely: axial velocity, temperature and mass fraction of carbon monoxide CO. Using commercial calculation software CFD Fluent The objective of this work is to research the fuel that reduces the emission of carbon monoxide CO, which is considered a gas toxic to the environment, by comparing the two fuels CH4 and C3H8. The results give methane fuel reduces carbon monoxide as a pollutant chemical species in combustion products compared to propane fuel.